27.7k views
3 votes
2(x−3)=8(x−6) take your time get it right please

1 Answer

3 votes

Answer: x=7



Step-by-step explanation: First to get rid of the parentheses we must multiply everything times 2 in the parentheses. Then we must also do the same with the other parentheses multiply everything by 8.


2(x−3)=8(x−6)


2x-6=8x-48


Then we subtract 8x from both sides.


2x-6=8x-48


-6x-6=-48


Then add 6 to both sides


-6x-6=-48


-6x=-42


Finally divide both sides -6


-6x/-6=-42/-6


x=7


Hope this helps!



User Acorbe
by
5.5k points